Who will pay amount A? - Michael P. Devereux; Martin Simmler (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2021)
Based on the agreed Pillar 1 threshold of profitability of 10% (and given that financial and extractive companies are excluded), then only 78 of the world's 500 largest companies will be affected. If the proportion of profit above this threshold liable to Amount A is set to 20% (from the range 20% to 30%) then the total allocation of Amount A for these companies would be 87 billion. Around 64% of this total (56 billion) would be generated by US-headquarted companies.Around 45% of this total(39 billion) would be generated by technology companies, and around 28 billion would be generated from the largest 5 technology US companies (Apple, Microsoft,Alphabet, Intel and Facebook). The decision to exclude financial companies reduces the total Amount A allocation by around half, although this is estimate is complicated by the different accounting treatment of banks.Reducing the revenue threshold from 20 billionto exteuro750 million (alongside Pil-lar 2) would double the aggregate Amount A butwould increase the number of companies affected by a factor of 13. The relative gain of reducing the threshold below 5 billion is small relative to the increase in the number of companies involved. Reducing the revenue threshold would have a less significant impact on companies in the automated digital services (ADS) and consumer facing business (CFB) sectors (the sectors that had been targeted in earlier proposals) than on companies outside those sectors. The sectoral composition of companies subject to Pillar 1 is strongly affected by the definition of profitability-pre-tax profits as a proportion of revenues. Among European firms with revenues above 20 billion, there are almost twice as many companies that have a return on equity above 10% compared to those that have a return on revenue above 10%.
Keywords: 330; Internationale Unternehmensbesteuerung; Internationales Steuerrecht; Steuerharmonisierung; Flat Tax; Besteuerungsverfahren; Rentabilität; Multinationales Unternehmen; Konzern; Welt